2014
DOI: 10.1016/j.rboe.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of life after vertebroplasty to treat compressive osteoporotic fractures

Abstract: Objectivewith increasing life expectancy around the world, fractures due to osteoporosis have become more common and the expenditure for treating them has also increased. The aim here was to evaluate the improvement in pain and quality of life among patients with compressive osteoporotic vertebral fractures undergoing vertebroplasty.Methodseighteen patients with 27 fractured vertebrae underwent vertebroplasty and were evaluated using the Oswestry 2.0 limitations questionnaire before the operation and 24 h and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…2 Vertebroplasty is effective in managing compressive osteoporotic vertebral fractures, with improvement in pain and quality of life in the immediate postoperative period and over the medium term. 3 Meta-analysis showed that PVA could relieve pain and improve spinal function more rapidly and notably than control treatment for osteoporotic vertebral compression fractures throughout 1-year follow-up. [4][5][6] The immediate outcomes of VP are well known, and it provides very important pain control.…”
Section: Discussionmentioning
confidence: 99%
“…2 Vertebroplasty is effective in managing compressive osteoporotic vertebral fractures, with improvement in pain and quality of life in the immediate postoperative period and over the medium term. 3 Meta-analysis showed that PVA could relieve pain and improve spinal function more rapidly and notably than control treatment for osteoporotic vertebral compression fractures throughout 1-year follow-up. [4][5][6] The immediate outcomes of VP are well known, and it provides very important pain control.…”
Section: Discussionmentioning
confidence: 99%